The effect of chitosan coating on post-harvest quality of banana in cold storage / Mohammad Nazrul Ali and Nur 'Amira Hamid - Ali, Mohammad Nazrul; Hamid, Nur 'Amira (Universiti Teknologi MARA Cawangan Pulau Pinang, 2021)
Banana (Musa acuminata) is a widely grown fruit crop in the tropical region. However, banana is climacteric and has relatively short storage life as well as being a highly perishable crop. The high respiration rate due to the rapid ripening from the production of ethylene in the fruit during storage and other post-harvest damage such as bruising, rotting, breaking, scarring and blemishes is the main factor that reduce the quality of harvested banana in the market. Due to that problem, the use of preservative and edible coating such as chitosan is important to improve the shelf -life of banana. This research is conducted to assess the effect of chitosan in maintaining the postharvest quality of banana stored in cold room. Three different concentrations of chitosan at 0.5%, 1.5% and 2.5% are used - one an experimental and the other two treatments as control where one control is without chitosan and stored in cold room, and the other control is coated with chitosan and stored in room temeprature. The quality evaluation is determined based on percentage of weight loss, total soluble solid (TSS), total acidity (TA) and storage time. The result showed that banana coated with chitosan can prolong the shelf-life and help maintain the quality of banana. Banana coated with 1.5% of chitosan exhibit less of total soluble solid and total acidity and prolong the shelf-life. These findings suggest that chitosan can be used as a coating agent for banana in storage for extending the shelf-life.